A new approach provides opportunities for spectral gamma analysis in boreholes for mineral exploration - Hooshyari-Far, I.; Kepic, Anton; Podolska, A. (Australian Society of Exploration Geophysicists, 2015)
Wide-spread application of gamma ray logging system in mineral exploration has long been desired by the mining industry, but not achieved. New developments in borehole logging approaches the Deep Exploration and Technologies Commonwealth Research Centre (DET CRC) have recently created Logging-While-Drilling tools, named the Autosonde and Shuttle, to measure natural gamma ray activity during drilling process. The Shuttle in particular will allow the collection of high quality natural gamma spectra by placing a sensor on the core-barrel and logging whilst drilling; a much slower process than wireline logging. Thus, a new approach collecting gamma data provides opportunities to use natural gamma radiation data in ways not normally done with conventional wireline tools. We have used a prototype spectral gamma sensor using BGO crystal on a wireline to simulate the data that will be collected by a shuttle system to demonstrate the data quality and to test whether more sophisticated data analysis of spectral attributes such as the ratio of Photo-electric to Compton gamma bands, or "heavy minerals indicator", will further lithological information than the standard K, U, Th analysis. Our preliminary results indicate that spectral data collected by the Shuttle will allow the heavy mineral indicator to be used and opens the possibility of better lithology identification tools.